COMPUTER-BASED MULTIMEDIA USAGE TRAINING - Agus Iskandar; Anugrah Pramuja (International Journal of Teaching and Learning, 2024)
This community service with the title "Training on the Use of Computer-Based Multimedia" aims to improve people's digital literacy and multimedia skills in the fast-paced digital era. This program is designed to teach participants how to integrate various forms of digital media such as text, images, video, and audio in their work and daily lives. This training involves a series of modules that include an introduction to multimedia, technical training, practical applications, and evaluation. Through a combination of face-to-face and online learning methods, this program has succeeded in reaching participants from various backgrounds, including teachers, MSMEs and the general public. Evaluation results showed significant improvements in participants' skills and confidence in managing multimedia content. More than 85% of participants reported substantial improvements in their ability to implement multimedia technology in their professional and personal practices. This service not only provides technical skills but also encourages innovation and technological adaptation in various aspects of life. Suggestions for future research include expanding the scope of training with the latest technology, improving infrastructure, and creating a wider collaboration network with the technology industry. This program provides a model that can be adapted and applied in various other societal contexts to increase the accessibility and effectiveness of digital education.